Synthesis and Characterization of 1,8-Naphthridine Derivatives - S. SAEED, MAY; E. AYOUB, ALAA; N. IBRAHIM, MOHAMED; M. EL-AJAILY, MAREI (Asian Journal of Chemistry, 2010)
1,8-Naphthridine derivatives were obtained by treatment of the condensation products of the aromatic aldehyde derivatives with 2-aminopyridine derivatives in presence of pyruvic acid.